The EIB Group Climate Bank Roadmap 2021-2025 November 2020 - European Investment Bank (European Investment Bank, 2020)
The EIB Group Climate Bank Roadmap 2021-2025 outlines our goals for climate finance that supports the European Green Deal and helps make Europe carbon-neutral by 2050. It maps the next stages in the journey to a sustainable planet and provides a framework to counter climate change.